Interpersonal Relation sebagai Variabel yang Menentukan Kinerja Unit atau Organisasi - J.A.A. Rumeser (Bina Nusantara University, 2010)
Every organization, require maintenance or improvement of performance for institutional sustainability. To maintain or improve performance, various kinds of business or methods developed. Various methodologies always involves a person or human element in organizations. Deepening and understanding of performance, will greatly assist the organization. When talking about performance in an organizational context, it is not sufficient if we only look at the paradigm in which individual capabilities we need to also look at the paradigm of interactions between individuals. To this we can turn to the model developed from HPT. From the discussion we propose a model that combines these two things, namely, the performance of (K) = individual resources (SDI) + interaction effectiveness (EI).